The “experience” of God - Barrajón Muñoz, Amador Pedro (Alpha omega, 2012)
The article presents the theme of the experience of God in the framework of a culture which gives a high value to experience. After examining two texts, one from the Old Testament and the other from the New, in which we find clearly expressed the value which divine revelation gives to religious experience, we examine the concept of experience from an etymological and philosophical point of view, and the need to give a further conceptual interpretation of lived experience. We then analyze a particular type of experience that is religious experience, and also what some theologians of the twentieth century have called "transcendental experience". In particular, we discuss the experience of faith and mystical experience, in a special way a particular situation which may occur that it is called the "noche oscura" (dark night of the soul). We then try to understand the value to be given to a particular type of experience that regards the certainty of the personal state of grace, which was a subject of dispute with the Reformers. Finally, we show the importance of the formation of a right conscience as a tool given by God to the person in order to provide a moral and religious assessment of their own spiritual experiences.